Blended (online and in‐person) Women's Health Interprofessional Learning by Simulation (WHIPLS) for medical and midwifery students. (18th April 2022) - Lee, Timothy; Yoon, Si Woo; Fernando, Shavi; Willey, Suzanne; Kumar, Arunaz
Abstract : Background: Blended teaching combines traditional in‐person components (simulation‐based training and clinical‐based placement) with online resources. Due to the COVID‐19 pandemic, we modified our Women's Health Interprofessional Learning through Simulation (WHIPLS) program – to develop core obstetric and gynaecological skills – into a blended teaching program. There is limited literature reporting the observations of blended teaching on learning. Aims: To qualitatively evaluate the blended teaching program and explore how it contributes to learning. Materials and Methods: This study was performed at Monash University in Melbourne, Australia. A total of 98 medical students and 39 midwifery students participated. Data were collected by written survey and analysed by authors using a thematic analysis framework. Results: Students reported that in‐person teaching remains a vital aspect of their curriculum, contributing an averaged 63.2% toward an individual's learning, compared with online. Five substantial themes demonstrate how students learnt and maximised education opportunities using a blended teaching program: 'low‐pressure simulation environments', 'peer‐assisted learning', 'haptic learning', 'scaffolded learning' and 'the impact of online discourse'. Discussion: In‐person teaching remains a cornerstone of obstetric and gynaecological clinical skills education, of which interprofessional simulation and clinical‐based placement are key components. Teaching via online discourse alone, is not sufficient to completely replace and provide comparable learning outcomes, but certainly plays an important role to prime students' learning and to maximise in‐person opportunities and resources. Our study reveals key pedagogies of a blended (online and in‐person) learning program, providing further evidence to support its ongoing utility as a feasible and warranted approach to learning.